Respuesta :

Answer:

The 2 numbers are 512.8 and 487.2.

Step-by-step explanation:

Let the numbers be x and y, then:

x + y = 1000............(1)

x^2 - y^2 = 25600

(x + y)(x - y) = 25600

1000(x - y) = 25600

x - y =  25.6............(2)

Adding (1) + (2):

2x = 1025.6

x = 512.8

so y = 1000 - 512.8

y = 487.2.

Answer:

512.8 + 487.2

Step-by-step explanation:

Let the two numbers be x and y respectively. The sum of x and y is 1000:

[tex]x+y=1000[/tex]

The difference between their squares is 25600:

[tex]x^2-y^2=25600[/tex]

We two unknowns(x and y) and two equations and therefore we can solve for x or y:

Lets:

[tex]x+y=1000[/tex]

and

[tex]x^2-y^2=25600[/tex]

We can simplify the expression as:

[tex](x+y)\cdot{(x-y)}=25600[/tex]

We can substitute x+y=1000 into this expression:

[tex]1000\cdot{(x-y)}=25600[/tex]

We can now write x in terms of y and vice verse, therefore:

[tex](x-y)=25600/1000=25.6[/tex]

[tex]x=25.6+y[/tex]

We have simple expression and can substitute it into x+y=1000

[tex]25.6+y+y=1000[/tex]

[tex]y=974.4/2=487.2[/tex]

therefore x can be solved by using the value of y and substituting it into x+y=1000:

[tex]x+487.2=1000[/tex]

[tex]x=512.8[/tex]